2020
DOI: 10.1016/j.msard.2020.102194
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Acute Necrotizing Encephalopathy Associated with RANBP2: Clinical and Therapeutic Implications in Pediatrics

Abstract: Genetic (also known as familial) acute necrotizing encephalopathy (ANE1) is a rare disease presenting with encephalopathy often following preceding viral febrile illness in patients with a genetic predisposition resulting from a missense mutation in the gene encoding RAN Binding Protein 2 (RANBP2). The acute episode is characterized by deterioration in consciousness, often with focal neurologic deficits and seizures. Additionally, symmetric multifocal brain lesions are seen in the bilateral thalami as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
78
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(92 citation statements)
references
References 59 publications
2
78
1
Order By: Relevance
“…Previous reports elucidated to a correlation between neuroradiologic lesions and outcome. Poor prognostic factors suggested by evidence at case series level are the presence of hemorrhage and cavitation, involvement of brainstem, bilateral as oppose to unilateral thalami and cerebral or cerebellar white matter [ 5 , 16 ]. It is worthwhile to mention that Sibling 3 who has all of these features recovered well without neurological sequelae.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous reports elucidated to a correlation between neuroradiologic lesions and outcome. Poor prognostic factors suggested by evidence at case series level are the presence of hemorrhage and cavitation, involvement of brainstem, bilateral as oppose to unilateral thalami and cerebral or cerebellar white matter [ 5 , 16 ]. It is worthwhile to mention that Sibling 3 who has all of these features recovered well without neurological sequelae.…”
Section: Discussionmentioning
confidence: 99%
“…A loss of function of RANBP2 results in disruption of cell processes, leading to cytokine dysregulation, breakdown of blood brain barrier and disordered oxidative phosphorylation and energy metabolism in neuronal cells. These translate clinically as increased risk of stress-induced neurotoxicity in the affected individual [ 5 , 7 , 11 ]. This disease is synonymously known as RANBP2 Susceptibility to Infection-induced Encephalopathy, Infection-induced Acute Encephalopathy 3 (OMIM 608033 ) and ANE1.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Acute necrotizing encephalitis (ANE) is a rare but severe disease with neurological complications triggered by possible viral or bacterial infections, with multifocal brain lesions, especially in the bilateral thalamus. Mizuguchi et al first described the form seen in childhood (acute necrotizing encephalitis of childhood; ANEC) in 1995 [1,2]. Although it has been reported with high rates from Japan so far, as a result of studies conducted worldwide, ANE has been observed to be not specific to a particular race [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%